Macrolactin A as a novel inhibitory agent for SARS-CoV-2 Mpro: bioinformatics approach - Bharadwaj, Kaushik Kumar; Sarkar, Tanmay; Ghosh, Arabinda; Baishya, Debabrat; Rabha, Bijuli; Kumar Panda, Manasa; Bryan Raveen, Nelson; Akbar John, B.; Sheikh Mohamed, Hassan Ibrahim; Dash, Bisnu Prasad; Atan Edinur, Hisham; Pati, Siddhartha (Springer Nature, 2021)
COVID-19 is a disease that puts most of the world on lockdown and the search for therapeutic drugs is still ongoing. Therefore, this study used in silico screening to identify natural bioactive compounds from fruits, herbaceous plants, and marine invertebrates that are able to inhibit protease activity in SARS-CoV-2 (PDB: 6LU7). We have used extensive screening strategies such as drug likeliness, antiviral activity value prediction, molecular docking, ADME, molecular dynamics (MD) simulation, and MM/GBSA. A total of 17 compounds were shortlisted using Lipinski’s rule in which 5 compounds showed significant predicted antiviral activity values. Among these 5, only 2 compounds, Macrolactin A and Stachyflin, showed good binding energy of −9.22 and −8.00 kcal/mol, respectively, within the binding pocket of the Mpro catalytic residues (HIS 41 and CYS 145). These two compounds were further analyzed to determine their ADME properties. The ADME evaluation of these 2 compounds suggested that they could be effective in developing therapeutic drugs to be used in clinical trials. MD simulations showed that protein–ligand complexes of Macrolactin A and Stachyflin with the target receptor (6LU7) were stable for 100 nanoseconds. The MM/GBSA calculations of Mpro–Macrolactin A complex indicated higher binding free energy (−42.58 ± 6.35 kcal/mol). Dynamic cross-correlation matrix (DCCM) and principal component analysis (PCA) on the residual movement in the MD trajectories further confirmed the stability of Macrolactin A bound state with 6LU7. In conclusion, this study showed that marine natural compound Macrolactin A could be an effective therapeutic inhibitor against SARS-CoV-2 protease (6LU7). Additional in vitro and in vivo validations are strongly needed to determine the efficacy and therapeutic dose of Macrolactin A in biological systems.